2022
DOI: 10.7454/ijphn.v2i2.5652
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Analysis of Wood Apple (Limonia acidissima)

Abstract: Wood apple or Limonia acidissima contains fruit acid, vitamins, and minerals. The dry fiber of the fruit contains 15% citric acid, potassium, calcium, and iron salt. The seed and pulp contain fats and protein. The fats consist of palmitic acid, oleic acid, linoleic acid, and linolenic acid, despite palmitoleic and stearic acid traces. β-sitosterol, β-Amirin, lupeol, and stigmasterol are from the unsaponifiable matter of seed oil. It was descriptive research that employed a laboratory experiment approach to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The energies of soy powders per 100 g was 450 kcal, containing 38.8% protein, 71.6% fat, and 11.3% fiber 38 . Meanwhile, wood apple contains 120 kcal/100 g, 3.5% protein, 2.5% fat, and 4.6% fiber 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The energies of soy powders per 100 g was 450 kcal, containing 38.8% protein, 71.6% fat, and 11.3% fiber 38 . Meanwhile, wood apple contains 120 kcal/100 g, 3.5% protein, 2.5% fat, and 4.6% fiber 39 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study determined that the wood apple fruit has a protein content of 4.3%. The study also found that proteins can undergo hydrolysis or breakdown into their constituent units, similar to other polymerized substances or compounds like triglycerides [ 20 ]. Another study has reported that wood apple fruits are high in protein, with a composition of 7.1% [ 25 ].…”
Section: Nutritional Profilementioning
confidence: 99%
“…Oil and fats are crucial substances that support human health. In addition, oil and fats are better suppliers of energy than protein and carbohydrates [ 20 ]. In a different study, it was found that wood apple fruits are rich in fat (3.7%) [ 25 ].…”
Section: Nutritional Profilementioning
confidence: 99%